Avaliação do deslocamento do processo alveolar fraturado: efeito da rigidez da contenção dentária - Paz, João Lucas Carvalho (2020)
Aim: measure the displacement of the alveolar buccal bone of a fractured region when it is compared to an intact region using an in vitro model with four teeth aiming observe the effect of the rigidity of a dental trauma splint Materials and Methods: to mimic a maxilla, four bovine incisors were placed in a plastic model made of polystyrene resin. To simulate the periodontal ligament (PDL), polyether was used. The fracture was designed in the model covering one tooth and the fractured bone was adhered to the model by the simulated PDL. The splints were created with four wires in different diameters (0.3, 0.6, 0.9 and 1.2mm). Models without splints were also tested. The measure of the displacement in the fractured region and in the intact region was made 3 times by a deflectometer (Instron) under a dynamic cycle with 100N on central incisor palatines. Data of the displacement were advised in micrometers and analyzed using Analyze of Variance followed by Tukey Test (α=0.05) Results: in relation to the intact alveolar process, the displacement in all situations of dental trauma splint were not different between them (P>0.05). The higher displacement found was in the without splint model and it was different of all other situations (P<0.001). When the diameter was increased, the displacement had been decreased (P<0.001). Dental trauma splints made with 0.9 and 1.2mm showed no difference (P=0.123). Conclusions: dental splint rigidity has shown influence on the fractured alveolar process mobility. The use of 0.9 mm and 1.2mm wire showed to be efficient to reduce the fractured alveolar process displacement when compared with the intact alveolar process.